Neural circuits controlling choice behavior in opioid addiction. (15th March 2023) - Chang, Victoria N.; Peters, Jamie
Abstract: As the opioid epidemic presents an ever-expanding public health threat, there is a growing need to identify effective new treatments for opioid use disorder (OUD). OUD is characterized by a behavioral misallocation in choice behavior between opioids and other rewards, as opioid use leads to negative consequences, such as job loss, family neglect, and potential overdose. Preclinical models of addiction that incorporate choice behavior, as opposed to self-administration of a single drug reward, are needed to understand the neural circuits governing opioid choice. These choice models recapitulate scenarios that humans suffering from OUD encounter in their daily lives. Indeed, patients with substance use disorders (SUDs) exhibit a propensity to choose drug under certain conditions. While most preclinical addiction models have focused on relapse as the outcome measure, our data suggest that choice is an independent metric of addiction severity, perhaps relating to loss of cognitive control over choice, as opposed to excessive motivational drive to seek drugs during relapse. In this review, we examine both preclinical and clinical literature on choice behavior for drugs, with a focus on opioids, and the neural circuits that mediate drug choice versus relapse. We argue that preclinical models of opioid choice are needed to identify promising new avenues for OUD therapy that are translationally relevant. Both forward and reverse translation will be necessary to identify novel treatment interventions. This article is part of the Special Issue on "Opioid-induced changes in addiction and pain circuits". Highlights: Here we review the neural circuits controlling opioid choice and relapse. We posit that preclinical choice models offer predictive validity. Both forward and reverse translation is needed to identify novel OUD therapeutics.